Noże z wczesnośredniowiecznego cmentarzyska w Sowinkach pod Poznaniem – ze studiów nad typologią i technikami kowalskimi - Krzyszowski, Andrzej (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
The article presents a typological analysis of a collection of iron knives comprising 70 specimens from the early medieval grave field in Sowinki near Poznań, dated back to the time between the second half of the 10th century and the early 12th century. Sixteen of the specimens were subjected to further metallographic analyses, carried out in the Casting Institute in Krakow. As a result, 4 major technological groups were identified with as many as 10 separate types. In half of the studied knives, the technology of welding iron and steel was used, i.e. steel in the form of an overlay or a “sandwich” in the classical variant. The analysis proved that the knives from the grave field represented the type of metal and technologies typical of the Vistula basin as well as the early medieval Kievan Rus’.